Use of complementary and alternative medicine and its related factors among pregnant women in Shiraz, South of Iran: A cross-sectional study - Hossein Molavi Vardanjani; Amie Steel; Darya Mofarrahi; Amir Mohammad Jaladat; Fatemeh Amini; Mahdi Zeraatpishe; Mehdi Pasalar (Wolters Kluwer Medknow Publications, 2023)
Background: Women are known to use Complementary and Alternative Medicine (CAM) during pregnancy despite the subsequent potential unknown effects associated with its use. This study was performed to evaluate the use of CAM products and its related factors among pregnant women in Shiraz, Iran. Materials and Methods: This cross-sectional study of 365 pregnant women referred to obstetrics clinics affiliated to Shiraz University of Medical Sciences (Iran) was conducted in 2020. Sampling was performed in all three affiliated centers based on a probability, proportional to size protocol. Pregnant women were nominated using a systematic random sampling scheme using their health record numbers. A 20-item questionnaire was administered via in-person interviews and data on demographics, use of CAM products, reasons for use, and referral and information sources were collected. Binary logistic regression was applied and adjusted odds ratios were estimated. Results: CAM use was reported for recent pregnancies by 56.92% of participating women, with a significantly higher use in participants of low socioeconomic status (Chi21 = 5.12; p < 0.024). The main reason for CAM use was having faith in the efficacy of CAM (72.73%). Reported CAM use was restricted to herbal preparations. Most of the women who used CAM (73.0%) did not report their CAM use to their doctor. Conclusions: There is a high rate of CAM use among pregnant women. More maternal care services during current pregnancy, parity, and general and pregnancy-related history of CAM use were correlated with CAM use. Mother-healthcare provider relationship should be improved in the field of CAM.